DNA methylation orchestrates secondary metabolite biosynthesis and transport in Papaver somniferum - Tuba Aksoylu; Mine Turktas (PLoS ONE, 2025)
Background Papaver somniferum (opium poppy) is a major source of benzylisoquinoline alkaloids (BIAs), including pharmaceutically important compounds such as morphine and noscapine. While the enzymatic pathways underlying BIA biosynthesis are well-characterized, the epigenetic mechanisms that govern tissue- and genotype-specific alkaloid accumulation remain poorly understood. Results This study presents a comparative DNA methylation analysis of stem and capsule tissues from P. somniferum cultivars with distinct alkaloid profiles. High-alkaloid-yielding cultivars exhibited hypomethylation of genomic regions involved in photosynthesis, carbon metabolism, protein phosphorylation, and intracellular transport, particularly in stem tissues. DNA methylation patterns revealed tissue- and compound-specific epigenetic signatures: morphine-rich cultivars showed enrichment of differentially methylated regions (DMRs) associated with membrane-related functions, whereas noscapine-rich cultivars exhibited DMR enrichment in nuclear regulatory components and ribosome-associated pathways. Genes encoding cytochrome P450 enzymes, F-box proteins, and ABC transporters were differentially expressed and epigenetically modulated, reflecting a multi-layered regulatory network coordinating biosynthesis, transport, and detoxification of alkaloids. Conclusions Our findings suggest that noscapine biosynthesis is under strict, evolutionarily conserved regulatory control, while morphine production is supported by transcriptional and metabolic enhancements in photosynthesis and carbohydrate metabolism. This study provides the first integrative epigenomic perspective on alkaloid biosynthesis in the opium poppy and highlights DNA methylation as a key determinant of metabolic specialization.